2005
DOI: 10.1590/s0100-06832005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de propriedades físicas do solo em uma parcela experimental

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
35
0
83

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 16 publications
12
35
0
83
Order By: Relevance
“…the range of spatial dependence for FdM was 9.7 m, so that the extreme values for the Bd and Ma ranged from 9.0 m (Bd2) to 38.0 m (Ma2c). these results were similar to those reported by Carvalho et al (2002Carvalho et al ( , 2003 and Grego & Vieira (2005), varying from 3.9 to 23.7 m (tp) and 1.0 to 13.1 m (Sd).…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…the range of spatial dependence for FdM was 9.7 m, so that the extreme values for the Bd and Ma ranged from 9.0 m (Bd2) to 38.0 m (Ma2c). these results were similar to those reported by Carvalho et al (2002Carvalho et al ( , 2003 and Grego & Vieira (2005), varying from 3.9 to 23.7 m (tp) and 1.0 to 13.1 m (Sd).…”
Section: Methodssupporting
confidence: 93%
“…diSCUSSion the variability of a property can be classified according to the magnitude of the variation coefficient (Freddi et al, 2006). in this study, the variability of FdM, Ma2c and the Ma3c was average, of Ma1 it was high and for the other variables low (table 1), in agreement with Carvalho et al (2002Carvalho et al ( , 2003, Johann et al (2004), Souza et al (2004a, b) and Grego & Vieira (2005). Soil variability is the product of interaction between the factors and processes of its formation, soil management and tilling.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The semivariograms adjusted by spherical, exponential e Gaussian functions presented spatial dependence for the majority of soil physical and chemical parameters, with prevalence of spherical adjustment model, in accordance with GREGO & VIEIRA (2005) who demonstrated that the spherical model was adjusted to all soil physical attributes, considered the major model in soil science studies (Figure 2). A spatial dependence for soil variables was not achieved only for penetration resistance (PR) measured in crop line, and for organic matter (MO), a phenomenon called "Pure Nugget Effect" (Table 2).…”
Section: Resultssupporting
confidence: 79%